Port placement in thoracoscopy - KB Galketiya; V Pinto (Anuradhapura Clinical Society, 2014)
Background: Thoracoscopy reduces the morbidity of open thoracotomy. The placement of camera and working ports is crucial for successful completion of the procedure. Methods: A retrospective review of video assisted thoracoscopic surgeries performed during January 2011 to June 2013 at the university surgical unit, Peradeniya, Sri Lanka was done. Port placement of each surgery was identified and the adequacy of space for dissection, use of additional ports for retractors, successful, comfortable and safe completion of the surgery with regard to average operative time, mean blood loss and conversions to open surgery were noted. Results: 9 different thoracoscopic procedures were performed on 67 patients. All procedures allowed comfortable dissection, adequate space for dissection and required no additional ports for retractors except for thymectomy and excision of retrosternal goiter. Time taken was acceptable with minimum blood loss and no conversions. Conclusion: For anterior and posterior mediastinal procedures the camera port was placed in the mid and the posterior axillary lines respectively and provided a clear display of the anatomy. The thirty degree camera was preferred as it provided a wider visual field. Working ports for anterior and posterior mediastinal procedures were placed in the anterior and mid axillary line respectively. Most effective placement for working ports were found to be two intercostal spaces above and below the camera port.